Modification of the SnO2 Electron Transporting Layer by Using Perylene Diimide Derivative for Efficient Organic Solar Cells - Kong, Tianyu; Wang, Rui; Zheng, Ding; Yu, Junsheng (Frontiers in Chemistry, 2021)
Recently, tin oxide (SnO2) nanoparticles (NPs) have attracted considerable attention as the electron transporting layer (ETL) for organic solar cells (OSCs) due to their superior electrical properties, excellent chemical stability, and compatibility with low-temperature solution fabrication. However, the rough surface of SnO2 NPs may generate numerous defects, which limits the performance of the OSCs. In this study, we introduce a perylene diimide derivative (PDINO) that could passivate the defects between SnO2 NP ETL and the active layer. Compared with the power conversion efficiency (PCE) of the pristine SnO2 ETL–based OSCs (12.7%), the PDINO-modified device delivers a significantly increased PCE of 14.9%. Overall, this novel composite ETL exhibits lowered work function, improved electron mobility, and reduced surface defects, thus increasing charge collection efficiency and restraining defect-caused molecular recombination in the OSC. Overall, this work demonstrates a strategy of utilizing the organic–inorganic hybrid ETL that has the potential to overcome the drawbacks of SnO2 NPs, thereby developing efficient and stable OSCs.